Productive and Destructive Entrepreneurship in a Political Economy Framework - Robin Douhan; Magnus Henrekson (Research Institute of Industrial Economics (IFN), 2008)
Recent research has highlighted the role of institutions in channeling entrepreneurs into activities with positive or negative effects on overall productivity. Embedding central elements from these theories into a political economy framework reveals the bilateral causal relation between entrepreneurs and institutions. Core features of the entrepreneur force us to view its effects on institutions as more than mechanic general equilibrium adjustments. Three analytically separate channels of influence are isolated, analyzed and exemplified. Entrepreneurs influence formal economic institutions through direct involvement in politics, by using their entrepreneurial talent to wield de facto political power and by altering the effect of formal institutions. We propose a parsimonious framework that incorporates these effects as well as the role of institutions in channeling entrepreneurial talent. We use examples from modern history as a real-world context to illustrate our framework.
Keywords: L50; M13; O31; P14; 330; Entrepreneurship; Innovation; Institutions; Regulation; Self-employment; Entrepreneurship-Ansatz; Innovation; Institutionelle Infrastruktur; Regulierung; Eigentumsrecht; Wirtschaftstheorie